COMMUNITY PARTICIPATION IN DIAPERS WASTE MANAGEMENT - Wahyuni Mayangsari; Nur Dyah Gianawati; Franciscus Adi Prasetyo; Atik Rahmawati (UPT Penerbitan Universitas Jember, 2022)
Diapers are anorganic waste and cannot be decomposed, waste management is needed. This study aims to analyze community participation in the management of diapers such as the form of community participation in its management in Taman Baru Village, Banyuwangi Regency. The method uses descriptive qualitative research. Data collection with unstructured interviews and direct observation. Furthermore, in determining informants use purposive. The results showed that the people in Taman Baru Village were very enthusiastic in participating in waste management. The form of participation is carried out as a donor of used diapers, involved in management and participates in socializing waste diapers management activities. However, the community is also still sorting out diapers that are worthy of being sent to the management site such as pee marks instead of fecal marks. For the surrounding community, used diapers (which feces on it) are not suitable for process, then people will throw it into landfills. So the need for education and training to the community in the management of diapers waste, so that this activity can be expanded. Of course, the goal of reducing diapers waste and protecting the environment can be realized.